Contaminants of legacy and emerging concern in terrestrial passerines from a nature reserve in South China: Residue levels and inter-species differences in the accumulation. (August 2015) - Peng, Ying; Wu, Jiang-Ping; Tao, Lin; Mo, Ling; Tang, Bin; Zhang, Qiang; Luo, Xiao-Jun; Zou, Fa-Sheng; Mai, Bi-Xian
Abstract: Knowledge is limited about the bioaccumulation of persistent halogenated compounds (PHCs) in terrestrial wildlife. Several PHCs, including dichlorodiphenyltrichloroethane (DDT) and its metabolites (designated as DDTs), polychlorinated biphenyls (PCBs), polybrominated diphenyl ethers (PBDEs), decabromodiphenylethane (DBDPE) and 1, 2-bis(2, 4, 6-tribromophenoxy) ethane (BTBPE), and stable isotopes (δ 15 N and δ 13 C) were analyzed in the muscle of four terrestrial passerines, Parus major, Copsychus saularis, Pycnonotus sinensis and Pycnonotus jocosus, from a nature reserve in South China. P . major had the highest PHC concentrations, with median values of 1060, 401, 92, 25 and 0.3 ng/g lipid weight for DDTs, PCBs, PBDEs, DBDPE and BTBPE, respectively. Fractions of DDT in P . jocosus and PCBs 153, 118 and 180 in C . saularis were higher compared with the other species. The inter-species differences in PHC concentrations and profiles could be attributed to the differences in trophic level, diet, living habits and metabolic capacity among the birds. Highlights: PHCs were investigated in terrestrial passerines from a nature reserve in China. DDTs were the predominant pollutants, followed by PCBs and PBDEs. Levels of PHCs generally increased with the increasing δ 15 N value. Inter-species differences in PHC profiles were observed. Abstract : Terrestrial passerines showed inter-species differences in concentrations and contaminant profiles of persistent halogenated compounds.